Optimization of Sp2hp in Improving Law Enforcement Transparency in Satreskrim Polrestabes Medan - Regi Putra Manda; Halimah Halimah (Badan Penerbit STIEPARI Press, 2025)
This study aims to 1) analyze the optimization of SP2HP in increasing transparency of investigations at the Medan Police Criminal Investigation Unit. 2) Identify obstacles faced in the implementation of SP2HP at the Medan Police. 3) Formulate strategies that can be applied to optimize SP2HP as a form of transparency in police services. The research method used in this study is document study. Document study is an in-depth method to explore phenomena in a particular system; Research Results 1) The implementation of SP2HP at the Medan Police Criminal Investigation Unit has been running according to regulations but still experiences obstacles in the issuance that is not on time and the lack of public understanding of the rights of the community as reporters in receiving SP2HP. Although SP2HP aims to increase transparency of investigations, complaints are still found regarding delays in its issuance and technological limitations in its delivery to the public. 2) Obstacles in the implementation of SP2HP, namely the main obstacles in issuing SP2HP to the reporter, are the high workload of investigators, the lack of socialization to the public regarding the rights of the public as reporters to obtain SP2HP, and the minimal use of digital technology to accelerate the process of submitting SP2HP. In addition, the absence of a strict monitoring mechanism for investigator compliance in issuing SP2HP is also an obstacle that causes less than optimal transparency in public services in the field of law enforcement, especially criminal investigations. The strategies that can be applied to increase the effectiveness of issuing SP2HP as an instrument to increase transparency in public services in the field of law enforcement are the following: a)Digitalization of the SP2HP system so that it can be accessed online by the public.b) Increasing investigator compliance in issuing SP2HP through internal audits and administrative sanctions for negligent investigators.c) Socialization to the public regarding the rights of the public as reporters to obtain SP2HP.